Gambaran Pola Makan dan Status Gizi Pasien dengan Gangguan Pencernaan di Puskesmas Selama Pandemi COVID-19 - Manurung, Novia Agustina; Hasneli N, Yesi; Erwin, Erwin (Publikasi Indonesia, 2022)
Digestive disorders are disorders that occur in the digestive tract. Digestive disorders that are often experienced by people are gastritis and dyspepsia. One of the main contributing factor of digestive disorders is eating habit. The purpose of this study is to describe the dietery habits and nutritional status of patients with digestive disorders at the Simpang Tiga public health center during the COVID-19 pandemic. This study used a descriptive research. The samples of this study were 93 patients with the diagnosis of gastritis and dyspepsia who were taken by purposive sampling technique. The data collection tool used a questionnaire that has been tested for validity and reliability. The result shows the eating habit of respondences for the types of eating habit much more of deficient are 65 (69,9%), the frequencies of eating much more of irregular are 57 (61,3%), and the amounts of food much more of irregular are 50 (53,8%). The nutritional status of respondences by the BMI classification much more categories as a normal, by the total of 47 (50,5%). The results of this study are to construct health promotion regarding to digestive disorders for the nurses.